Strategi Manajemen Program Pendidikan Islam yang Berorientasi pada Mutu - Moh. Ichsan Zaelani; Awwal Muzakki (JMPI: Jurnal Manajemen Pendidikan Islam, 2025)
This study examines the management strategies of Islamic education programs focused on quality, with a particular emphasis on best practices, challenges, and factors that support successful implementation. The research employs a qualitative approach through a literature review, analyzing books, journals, articles, and educational policy documents. The findings indicate that effective program management includes student-centered planning, innovative curriculum development, professional human resource management, utilization of technology, and continuous evaluation and monitoring. The success of implementation is influenced by visionary leadership, managerial support, collaboration among teachers and staff, curriculum innovation, technology integration, and active involvement of students and the community, while obstacles arise from limitations in human resources, facilities, and infrastructure, organizational culture, regulations, and inter-institutional competition. These findings underscore the importance of mitigation strategies and the reinforcement of supporting factors to enhance the quality of Islamic education sustainably. Keywords: program management, Islamic education, educational quality, management strategies